A state-of-the-art review on international strategic alliances: do we really know what we are researching? - Silva, Susana C. (2022)
This review explores recent literature on international strategic alliances (ISAs). Management of alliances requires a better understanding of different dimensions and components of ISAs and of their role. This review provides a state-of-the-art understanding of the concept using content analysis of 85 ISA articles. There is limited research on the concept of ISA and the components that affect the alliances’ formation, post-formation and outcome. We found notable inconsistencies in the ISA literature on the concept. This highlights the need for further structuration of the concept and the need to provide characterisation that is more coherent. This review presents implications for the definition and future research avenues for the concept, especially regarding the theory, context and the scope of ISA research. Finally, this study provides a state-of-the-art discussion that proposes critical viewpoints for future development of the concept of ISAs, their influential components and their application in research and international management.